Freshwater flux from ice sheet melting and iceberg calving in the Southern Ocean. (14th March 2017) - Hammond, Mark D.; Jones, Daniel C.
Abstract : This dataset is a multiyear mean Southern Ocean freshwater flux field that uses recently compiled measurements of ice sheet melting, iceberg calving, iceberg tracking, and river runoff. It has a horizontal resolution of 1/6° and uses BEDMAP2 for identifying and placing individual ice sheets. The aim of this work is to improve the representation of Antarctic freshwater input in Southern Ocean models.